A Problem Based Learning: Practicing Students' Critical Thinking Skills with Cognitive Style Dependent Fields and Independent Fields - Wahyu Listiagfiroh; Ellianawati Ellianawati (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2019)
The critical thinking skills require to be possessed by students to decide to gain new knowledge. The perception differences by each student influence students' thinking skills have, so to practice these skills is a needed learning approach to the student truly. One of them is problem-based learning. The purpose of this study is to train students' critical skills who have the cognitive method of Field Independent (FI) and Field Dependent (FD). This type of research is experimental research. The sampling technique in this study uses a cluster random sampling technique, which is taking random group samples. The results of this study are (1) the average Islamic Nurul Hadi Vocational School students belong to the dependent field cognitive style (FD); (2) the majority of students' critical thinking skills are in the high category, in 26 students consisting of 19 FI students and 7 FD students; (3) FI students are better at critical thinking compared to FD students. FD students need guidance in solving problems. PBL learning model is very appropriate to be used to train students' critical thinking skills with different cognitive styles.